The Effect of Time of Sulphur Fertilizer Applcation on the Growth, Yield and Seed Quality of Oilseed. Rape (Brassica Napus L) Grown Under Glasshouse Conditions (Journal of Science and Technology, 2016)
A glasshouse experiment was carried out to investigate the effect of varying the timing of Sulphur fertilizer application on the morphology, reproductive structure and seed quality of oilseed rape (Brassica napus). Sulphur as potassium sulphate was applied at five growth stages to provide information on the response of the winter oilseed CV. Ariana. Results demonstrated that dry matter production, number of pods per plant, seed yield and glucosinolate concentration were increased by Sulphur application. The response was greatest when 2OmgS/kg soil was applied at green bud or Growth stage 3.3 (T4). Seed oil and protein percentages were not influenced by the treatments.